Digest: Unlocking the creative potential of specialization*. (2nd May 2019) - Linscott, Jennifer
Abstract: Do constant environments produce ecological specialists? Wang et al. test this common assumption in Drosophila melanogaster and find that the converse may be true: constant environments sometimes produce robust generalists that can withstand change. In this study, increased tolerance to change may be best explained as a by‐product of adaptation to a particularly harsh salt‐enriched environment.